Zooplankton Distribution and Species Diversity in Myponga Reservoir, South Australia - Ismail, Azma Hanim; R., Shiel; F., Recknagel (GCAEER, 2013)
Myponga Reservoir is a water storage that supplies drinking water to the southern metropolitan area. It is a highly managed water body with prolonged artificial mixing and regular algicide dosing (CuSO4) to manage water quality problem. The total number of taxa in Myponga was 16 and Cladocera was the dominant taxonomic group in relation to the total number of taxa. In terms of total density, Copepoda were the numerically dominant group in both reservoirs. The most frequently occurring Cladocera were Ceriodaphnia cf. quadrangula, Ceriodaphnia cornuta and Bosmina meridionalis while Asplanchna priodonta was the predominant Rotifera throughout the study. Copepoda were dominated by Calamoecia ampulla and Microcyclops sp., making up the largest portion of total zooplankton density. Observations showed relatively consistent species diversity and density throughout the study in Myponga Reservoir except for low densities during summer for Cladocera and Copepoda groups. Shallow locations have greater zooplankton densities compared to deep locations in the reservoir. Biological factors including the occurrence of green algae and cyanobacteria may influence zooplankton abundance and the dynamics of the community.